Mechanical Stretch Induces mTOR Recruitment and Activation at the Phosphatidic Acid-Enriched Macropinosome in Muscle Cell - Lin, Shan-Shan; Liu, Ya-Wen (Frontiers in Cell and Developmental Biology, 2019)
The mammalian target of rapamycin (mTOR) is an evolutionarily conserved kinase which assembles a signaling network that integrates diverse biochemical and mechanical cues to coordinate cell growth and proliferation. Mechanical load has been well appreciated to induce mTOR activation that leads to skeletal muscle growth through phospholipase D (PLD) activity and phosphatidic acid (PA) production. While PA produced by PLD1 is critical for mTOR activation upon mitogenic stimulation at the lysosome, it is unclear where PA is produced upon mechanical stimulation in skeletal muscle. Here we report that membrane tension surge induces the formation of PA-enriched macropinosome in mouse C2C12-derived myotube by either mechanical stretch or osmotic shock. The tension surge-induced PA is accumulated at the membrane of macropinosome, not the lysosome. Furthermore, mTOR is recruited to the PA-enriched macropinosome, and its downstream signaling is activated. Our findings reveal the underpinning of mechanical activation of mTOR signaling, and more importantly, the stretch-induced PA-macropinosome as a new platform for mTOR activation.